Role of trpv1 (transient receptor potential v1 channel) in piperine induced hyperalgesia: a preliminary study - Gohil, Priyanshee; Shah, Gaurang; Patel, Chhaya (International Journal of Pharmacology and Toxicology, 2014)
Background: The inflammatory disease is associated with chronic pain and hypersensitivity to noxious stimuli in form of hyperalgesia. Transient receptor potential vanilloid type-1 (TRPV1) activated by various inflammatory mediators; plays a key role in occurrence of hyperalgesia. Piperine is the primary pungent alkaloid of Piper nigrum. Piperine has common binding site with capsaicin (TRPV1 agonist) on TRPV1 and it has more efficacy for activation of TRPV1 than capsaicin. Objective: The purpose of the study was to investigate the role of TRPV1 in piperine induced hyperalgesia in diabetic mice. Methods: Diabetes mellitus was induced in mice using streptozotocin (STZ). Nociception was measured by three types of thermal nociceptive tests (Hot plate method, radient heat tail-flick method and tail immersion test). Pilot study (using 2.5, 5, 10 and 50 mg kg-1 piperine, i.p.) was carried out and 5 mg kg-1 piperine is used as optimum dose for further study. Capsaicin, capsazepine and piperine were administered to their respected groups and nociceptive threshold was noted on day 4, 7 and 10 in all groups. Results: Piperine showed a significant decrease in nociceptive threshold as compared to diabetic control group, while there was a significant increase in reaction time, tail flick latency and tail withdrawal latency, in the animals pre-treated with capsazepine before piperine administration as compare to only piperine treated diabetic group. Conclusion: Activation of TRPV1 might be one of the possible mechanisms of Piperine induced hyperalgesia. Keywords: Capsaicin, Capsazepine, Hyperalgesia, Nociceptive Threshold, Piperine, TRPV1.